The Determinants of leisure attitudes: Mediating effect of self-efficacy among students from science, engineering and medicine colleges - Jdaıtawı, Malek; Rasheed, Abeer; Goharı, Mohamed; Raddy, Yasser; Aydın, Mehmet; Abas, Ahmed; Hasan, Abdelmonim; Khatıry, Ahmad (Journal of Turkish Science Education, 2020)
This resent study investigated the relationships between leisure attitude, self-efficacy and achievement motivation among first year university students. Furthermore, this study examined the mediating role of self-efficacy on the relationship between leisure attitude and achievement motivation among university students. A total of 190 students were selected from Imam Abdulrahman Bin Faisal University using cluster sampling method. The questionnaires consisted of the revised version of the self-efficacy scale, leisure attitude measure and achievement motivation measure. The results revealed that there were significant positive relationships between the study variables. additionally, the result also showed that self-efficacy partially mediated the achievement motivation-leisure attitude relation. The implication is that students’ abilities should be improved by promoting leisure activities which may motivate them to participate in the learning activities.